2022
DOI: 10.52812/msbd.47
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Perceived Performance of Solar-Powered Borehole Projects in Nigeria

Abstract: This study aimed at the assessment of the perspective of the people of Kano-south senatorial district, Nigeria on solar powered borehole projects. This research sought to establish the performance of solar-powered boreholes in terms of presence, their importance, their performance, and maintenance culture as well as provide solutions to possible problems that the senatorial district may be encountering in the usage of these amenities to ensure good sustainability. The survey research method was adopted for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The current study adopted the survey research method, and the flowchart is shown in Figure 2. It is defined as collecting data by sending a questionnaire to relevant persons [20]. In this case, the relevant persons are the petroleum filling station attendants in Kaduna Metropolis, Nigeria.…”
Section: Methodsmentioning
confidence: 99%
“…The current study adopted the survey research method, and the flowchart is shown in Figure 2. It is defined as collecting data by sending a questionnaire to relevant persons [20]. In this case, the relevant persons are the petroleum filling station attendants in Kaduna Metropolis, Nigeria.…”
Section: Methodsmentioning
confidence: 99%